(untitled) (Diversity Research: Journal of Analysis and Trends, 2024)
In the world, attention is being paid to the introduction of consistency and systematicity in the process of managing general secondary schools, the effective use of modern technologies of resource management in an innovative educational environment. In particular, in the conditions of innovative education, the development of modernization mechanisms of management, the introduction of rapid assessment tools and quality and efficiency monitoring strategies in the general secondary education system are of urgent importance. This article talks about the content of improving the management process of general secondary schools in the context of modernization of education